Kajian Asuhan Keperawatan Pada Kkeluarga Tn.S Dengan Gangguan Pernafasan:Masalah Utama Asma di Desa Mangkuyudan Kartasura Wilayah Kerja Puskesmas I Kartasura - Mufidin, Faqih, Abi Muhlisin, SKM., M.Kep (2015)
Background: Asthma is a disease in the community that is considered trivial, but the disease can cause death in Kartasura health centers to get the data of people affected by asthma, there were 223 new cases and 30 old cases with 16 family cards are divided 163 women and 106 men who were in there are 247 in the region and in the region there are 22 and the number of overall asthma is 269 people. Objective: To determine the nursing care at keluarag members with asthma include assessment, data analysis, intervention, implementation and evaluation of nursing. Results: after the nursing care during each visit 3x visit 60 minutes is obtained, able to recognize the problem of asthma, take the right decision, no longer buy drugs in shops but in health care, modify the environment. Conclusion: cooperation among the family health team is indispensable for the success of keperawatn care, therapeutic communication can encourage more cooperative keluargaa. Given this can solve the problem of nursing acute pain associated with the family's inability to care for family members with asthma and recurrent risk of recurrence associated with the inability of families to know the problem of hypertension. Keywords: asthma, the risk of complication